VALIDITY ANALYSIS OF ANDROID-BASED DISCOVERY LEARNING LEARNING MODEL TO IMPROVE THE UNDERSTANDING OF THE PHYSICAL CONCEPTS - Moh Apandi G Jaapar; Abdul Haris Odja; Trisnawaty Junus Buhungo (INSECTA: Integrative Science Education and Teaching Activity Journal, 2020)
This study aims to determine the validity of the discovery learning model assisted by android-based crossword puzzle media in order to see the improvement in the concept of physics. This increase can be seen from the results of the validity of the instrument whether or not the instrument used is feasible. This research method is development research (Dovelopmental Research) with the development design  which consists of (1) instructional problems, (2) learner charity, (3) task analysis, (4) instructional, (5) content sequencing , (6) instructional strategic, (7) instructional delevery, (8) evaluation instruments, and (9) instructional response. The results obtained through two validator experts, the validated device was included in the very valid criteria, so it could be concluded that the instrument was very suitable for use.